The new stochastic solutions for three models of non-linear Schrödinger’s equations in optical fiber communications via Itô sense - Alkhidhr, Hanan A. (Frontiers in Physics, 2023)
In this paper, we consider three models of nonlinear Schr\"odinger's equations (NLSEs) via Itô sense. Namely, we study these equations forced by multiplicative noise via Brownian motion process. There are numerous approaches for converting nonlinear partial differential nonlinear equations (NPDEs) into ordinary differential nonlinear equations (ODEs) to extract wave solutions. The majority of these methods are a type of symmetry reduction known as nonclassical symmetry. We apply the unified technique that based on symmetry reduction to produces some new optical soliton solutions for the proposed equations. The gained stochastic solutions depict the propagation of waves in optical fiber communications. The theoretical analysis and proposed results clarify that the presented technique is sturdy, appropriate and efficacious. Some graphs of selected solutions are also depicted with the help of Matlab packet program. Indeed, the structure, band width, amplitude and phase shift controlled by the influences of physical parameters in the presence of noise term via Itô sense. Our results show that the proposed technique is better suited for solving many other complex models arising in real-life problems